Elite road vs. trail runners: comparing economy, biomechanics, strength, and power - Sabater Pastor, F.; Besson, T.; Berthet, M.; Varesco, G.; Kennouche, D.; Dandrieux, P. E.; Rossi, J.; Millet, G. Y. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to determine the differences between road (ROAD) vs. trail (TRAIL) elite runners in terms of force-velocity profile (FVP), running biomechanics, lower-limb maximal isometric strength, cost of running (Cr), and training. Seventeen male elite athletes (10 TRAIL and 7 ROAD) participated in this study. Force-velocity profile was measured using a 2-sprint test on a cycle ergometer. Strength was assessed with a dynamometer measuring isometric maximum voluntary torque of the knee extensors and knee flexors. Biomechanics parameters (running kinematics and stiffness) were measured, and Cr was calculated at 10 and 14 km/h at 0% slope and at 10 km/h on a 10% slope on a treadmill. Athletes also reported their training duration during the previous year. Theoretical maximal torque (F0) and maximal power (Pmax) in the FVP were higher for TRAIL vs. ROAD (122 ± 13 vs. 99 ± 7 N·m, p = 0.001; and 726 ± 89 vs. 626 ± 44 W; p = 0.016). Cost of running was higher for TRAIL compared with ROAD on flat at 14 km/h (4.32 ± 0.22 vs. 4.06 ± 0.29 J/kg/m; p = 0.047) but similar at 10 km·h-1 and uphill. No differences were found in maximal isometric strength or running biomechanics. ROAD spent 81% more time training than TRAIL (p = 0.0003). The specific training (i.e., "natural" resistance training) performed during graded running in trail runners and training on level surface at high speed may explain our results. Alternatively, it is possible that trail running selects stronger athletes because of the greater strength requirements of graded running.